Design and Control of Bioinspired Millibots. (5th June 2020) - Reghu, Sheethal; You, Hui; Seenivasan, Kalaivani; Nishimura, Shun; Taniike, Toshiaki; Miyako, Eijiro
Abstract : In the last decade, there has been great progress in the field of smart materials and technologies for the development of bio‐inspired artificial insects. An insect‐mimetic functional nanocomposite, namely, millimeter‐sized robot (millibot), based on magnetite, zeolitic imidazolate framework‐8, and polytetrafluoroethylene is successfully prepared. The millibots are designed through a rational chemical design for controlling its multi‐functions by external light and magnetic field, which act as fuels. The millibots can be effectively loaded with CO2 gas and remotely controlled by photothermal energy for the release of CO2 molecules from the laser‐induced millibots to anesthetize fruit flies as a potential foreign enemy. A remote regulation of the photo‐ and magnetic field‐induced millibot dynamic locomotion is demonstrated. As a proof of principle, millibots equipped with a gelatin particle encapsulating rhodamine B are efficaciously used in the bio‐inspired spawning of an artificial insect. The materials and strategies could inspire new designs for the development of high‐performance biologically active insect‐type robots in the future. Abstract : Millimeter‐scaled artificial insects (millibots) composed of rationally designed chemical materials including magnetite (MAG), zeolitic imidazolate framework‐8 (ZIF‐8), and polytetrafluoroethylene (PTFE) are developed for remote controlling their multi‐functions by external light and/or magnetic field.